New Catastrophic Gas Blowout and Giant Crater on the Yamal Peninsula in 2020: Results of the Expedition and Data Processing - Vasily Bogoyavlensky; Igor Bogoyavlensky; Roman Nikonov; Tatiana Kargina; Evgeny Chuvilin; Boris Bukhanov; Andrey Umnikov (Geosciences, 2021)
This article describes the results of an Arctic expedition studying the new giant gas blowout crater in the north of Western Siberia, in the central part of the Yamal Peninsula in 2020. It was named C17 in the geoinformation system “Arctic and the World Ocean” created by the Oil and Gas Research Institute of the Russian Academy of Sciences (OGRI RAS). On the basis of remote sensing, it can be seen that the formation of the crater C17 was preceded by a long-term growth of the perennial heaving mound (PHM) on the surface of the third marine terrace. Based on the interpretation of satellite images, it was substantiated that the crater C17 was formed in the period 15 May–9 June 2020. For the first time, as a result of aerial photography from inside the crater with a UAV, a 3D model of the crater and a giant cavity in the ground ice, formed during its thawing from below, was built. The accumulation of gas, the pressure rise and the development of gas-dynamic processes in the cavity led to the growth of the PHM, and the explosion and formation of the crater.